Análise do efeito de crises sobre estratégias de pairs trading no Brasil - Oliveira, Adriano Gonçalves de (2017)
The purpose of this work is to check the performance of the distance method of the pairs trading strategy in the Brazilian market. The study takes place in the period between 2004 and 2017, trying to identify if these strategies brought consistent returns despite several economic and political crises. Unlike the vast literature that seeks more complex models that can act in pairs trading strategies, this study will focus only on the method of distance, without the incidence of transaction costs, in this most recent horizon not yet studied. For being relatively simpler, this method has a higher attractiveness practice. Therefore, it is necessary to understand your behavior in a crisis. The methodology used was extracted from Gatev et al. (2006) and Rad, Low and Faff (2012) articles with only a change in the criteria for closure of positions. As a result, the studied strategy did not present statistically significant losses in times of crisis.